Influence of Teacher Experience on School Academic Performance in Kenya Certificate of Secondary Education in Kisii Central Sub-County, Kenya - , Matoya Haron Mageka; George Ogochi (IJRDO- Journal of Educational Research, 2020)
Teachers have a crucial role in improving learning outcomes. Since quality differs by teacher, their potential impact on student outcomes may also differ. The study explored the influence between teacher experience and school academic performance in Kisii Central Sub-County, Kisii County, Kenya. The study was carried out in Kisii central Sub-County which has 61 public Secondary schools and 13 private secondary schools. The study utilized mixed methods approach and concurrent triangulation design where qualitative data utilized an Ex post facto design while qualitative used correlational research design, then the two types of data were triangulated within the same time frame. The target population was 965 respondents comprised of all the 888 Secondary school teachers and principals in the 61 public secondary schools and 13 private schools in Kisii central Sub-County. The study used a sample size of 195 respondents (14 principals, 3 Area Education Officers and 178 teachers) using the central theorem. Data was collected through questionnaires, interview guide and document analysis. The instruments were piloted in 10 randomly selected secondary schools in the neighbouring Kitutu Chache Sub-County. The instruments validation exercise was done by the supervisors. A test- retest reliability technique was used to determine the reliability of the instruments where a coefficient of 0.76 was established. Descriptive statistics and inferential statistics were used to analyze data. Data was then presented through tables while bivariate analysis using Pearson Product Moment Correlation Coefficient to test if there was any relationship between teacher dynamics and student academic performance respectively. The findings of the study revealed that Teacher’s experience, teacher’s qualification, teacher’s preparedness and teacher professional development positively and significantly influence academic performance of the learners/schools. In conclusion, teacher dynamics contributes 33.3% variability to the academic performance of the students.